Erliquiose canina: revisão de literatura - Isola, José Geraldo Palma [UNESP]; Cadioli, Fabiano Antonio [UNESP]; Canesin, Ana Paula Massae Nakage (My University, 2012)
The hemoparasitosis ehrlichiosis is a disease with high incidence in veterinary clinic routine, which causes damage to animal and human health, thus requiring the rapid and accurate diagnosis for treatment witch consists of specific drugs in particular doxycycline. It is necessary to make a good prevention, to prevent the disease, especially with regard to the control of ticks, since this is the vector of the agent. This review aims to elucidate the details for the canine ehrlichiosis, as a tool to help veterinarians to better understanding of this disease.

A erliquiose é uma hemoparasitose infecto-contagiosa de alta incidência na rotina clínica veterinária, que causa prejuízos à saúde animal e humana, fazendo-se necessário o diagnóstico rápido e preciso para o tratamento que é realizado com drogas específicas em especial a doxiciclina. É necessário que se faça uma boa prevenção, para se evitar a doença, principalmente no que diz respeito ao controle dos carrapatos, uma vez que este é o vetor do agente etiológico. Esta revisão tem por objetivo elucidar as particularidades sobre a erliquiose canina, como ferramenta de ajuda aos médicos veterinários para maior conhecimento desta enfermidade.
Canine ehrlichiosi: literature review
Keywords: Ehrlichiosis; Dog; Hemoparasitosis; Serology; Dot-Blot ELISA; Erliquiose; Cão; Hemoparasitose; Sorologia; Dot-Blot ELISA